Application of SAW in the Class Leader Selection Decision Support System - Muhammad Najib Dwi Satria; Mahardika Inka Takaendengan (PT. Tech Cart Press, 2023)
The election of the class president is one of the activities that is often carried out when students are in school. A class in school can be interpreted as a country that has a government system. So, it is very important for a class to have a leader. Usually the election of the chairman is done by voting from class members. Later as a chairman, you will have various obligations. Simple Additive Weighting (SAW) is a method that is often known as the weighted sum method. Based on the needs gathering, an approach is proposed using a decision support system using the SAW method in selecting class leaders. There are 4 criteria used in selecting class leaders. The purpose of the weighted sum is to find the weighted sum of the ratings in each alternative on all criteria. Based on the calculation results using SAW for the election of the class leader, the 1st rank of the class leader election is Ahmad Jatmiko with a score of 0.99. Ranked 2nd in the class leader election was Muhammad Akbar with a score of 0.9. And ranked 3rd in the class leader election is Siti Setianingsih with a score of 0.8525.